Educación literaria: controversias pedagógicas entre el Ministerio de Educación y Ciencia y la Asociación de Profesores de Portugués - Resende, José Manuel; Carvalho, José Maria (Pedagogía y Saberes, 2019)
This paper addresses the conflict raised by the reformulation of the Portuguese language program in secondary education. This reform was put to the test by the Ministry of Education of Portugal in 2013. From the controversies raised by the changes made, we chose literary education and the criteria to choose literary works for school as a topic of discussion. The program’s design is subject to a lively discussion among credible actors. In this article, we combine a reflection and an exploratory research and chose the controversies incurred by the Portuguese Teachers Association in opposition to Government-issued guidelines. From the discussion, we highlight the opposition to the canon as a criterion for choosing the works and how inference can be operated in a massified school and with the compulsory length of school until the twelfth year.